PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL DAN MOTIVASI TERHADAP HASIL BELAJAR SENI BUDAYA SUB BIDANG STUDI SENI RUPA SISWA KELAS VII SMPN 6 SUNGAI PENUH - WIWIN MUKTI SAPUTRA, Dr. Ramalis Hakin, M.Pd., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2017)
Student learning outcomes for subjects of Arts Culture sub-field of Art Studies students class VII in SMPN 6 Sungai Penuh not satisfactory. For that done efforts to improve learning outcomes by using audio visual media in the learning process. This study aims to describe the effect of audio visual media usage and motivation on the result of Art Culture learning in the field of Fine Arts study of class VII students at SMPN 6 Sungai Penuh.The research method used is quasi experimental (experimental quasi) with faktorial 2 × 2 research design, with sample determination using purposive sampling technique. Researcher get class VII / A as experiment class and class VIII / B as control class. The data collection is done through questionnaire instrument of learning motivation and test result of learning, the test used needs to be seen first the index of difficulty, distinguishing power, and reliability. The data analysis technique is descriptive processing and inductive analysis using SPSS v.18.Based on the hypothesis test the results obtained 1) Sig-alpha (0.000 <0.05) and t arithmetic greater than t table (4.764> 2.021), then Ho is rejected and and H1 accepted, thus the experiment class learning outcomes differ significantly Learning result of control class, 2) Sig-alpha (0,012 <0,05) and t count bigger than t table (3,081> 2,228), hence Ho is rejected and and H1 accepted, thus learning result of learning motivation high class experiment differ (3) sig-alpha (0,016 <0,05) and t count bigger than t table (2,884> 2,228), hence Ho is rejected and H1 accepted, thus result of learning Low motivation learning experimental classes differ significantly compared to the students' learning outcomes of low motivation learning experiments.The study concluded that the use of audio visual learning media has a positive effect on the students' learning outcomes in the learning of Cultural Arts in the field of art study in the seventh grade of SMPN 6 Sungai Penuh.Keywords : Audio Visual Media Learning and Motivation, Student Learning Resul